Pemanfaatan Sistem Informasi Kesiswaan Berbasis Teknologi Informasi dan Komunikasi dalam Pengelolaan Data Administrasi Siswa di SMP Muhammadiyah Bligo Kabupaten Pekalongan - Supriyadi, M. Yusup; Khikmah, Eni Nur; Murtiyasa, Budi; Masduki, Masduki (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The use of Information and Communication Technology (ICT) in school administration management is one of the strategic efforts to increase the effectiveness and efficiency of educational services. One form of ICT utilization is the application of student information systems in the management of student administrative data. This study aims to determine the effectiveness of the use of ICT-based student information systems in the management of student administrative data at Muhammadiyah Bligo Junior High School, Pekalongan Regency. This study uses a quantitative approach with a descriptive method. Data is collected through questionnaires given to education personnel who are directly involved in the management of student administration. The effectiveness indicators used include ease of data management, speed of access to information, accuracy and accuracy of data, and neatness and security of administrative archives. The data obtained was analyzed using quantitative descriptive analysis techniques by calculating the average score on each indicator. The results of the study show that the use of ICT-based student information systems at Muhammadiyah Bligo Junior High School, Pekalongan Regency is in the effective category. The student information system is able to facilitate the management of student administrative data, accelerate access to information, improve the accuracy and accuracy of data, and maintain the neatness and security of administrative archives. Thus, it can be concluded that the use of ICT-based student information systems plays an important role in supporting the improvement of the quality of student administration management in schools.